2023
DOI: 10.1080/22423982.2023.2192392
|View full text |Cite
|
Sign up to set email alerts
|

Performance nutrition for cold-weather military operations

Abstract: .High daily energy expenditure without compensatory increases in energy intake results in severe energy deficits during cold-weather military operations. The severity of energy deficits has been proportionally linked to declines in body mass, negative protein balance, suppression of androgen hormones, increases in systemic inflammation and degraded physical performance. Food availability does not appear to be the predominant factor causing energy deficits; providing additional rations or supplement snack bars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Work [4] reports the study of energy supply issues for Norwegian military personnel under cold conditions. It is noted that physical exertion in cold weather leads to a serious energy deficit during military operations.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Work [4] reports the study of energy supply issues for Norwegian military personnel under cold conditions. It is noted that physical exertion in cold weather leads to a serious energy deficit during military operations.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Cold-weather military operations, such as those described above, result in high daily energy expenditures. Based on results obtained from winter military exercises in Norway, Margolis and Pasiakos [ 31 ] noted that soldiers failed to achieve energy balance, resulting in severe energy deficits, which caused negative physiological effects that ultimately lead to reductions in physical performance. They concluded that higher-fat energy dense food products are a viable nutrition intervention to minimise the severity of energy deficits to sustain physical performance.…”
Section: Metabolic Balance and Stress In Field Training In The Coldmentioning
confidence: 99%